Assessment of high-confidence protein-protein interactome in yeast - ARĞA, KAZIM YALÇIN (ELSEVIER SCI LTD, 2013)
The identification of protein-protein interactions (PPIs) and their networks is vitally important to systemically define and understand the roles of proteins in biological systems. In spite of development of numerous experimental systems to detect PPIs and diverse research on assessment of the quality of the obtained data, a consensus - highly reliable, almost complete - interactome of Saccharomyces cerevisiae is not presented yet. In this work, we proposed an unsupervised statistical approach to create a high-confidence yeast PPI network. For this, we assembled databases of interacting protein pairs for yeast and obtained an extremely large PPI dataset which comprises of 135 154 non-redundant interactions between 6191 yeast proteins. A scoring scheme considering eight heterogeneous biological features resulted with a broad score distribution and a highly reliable network consisting of 29 046 physical interactions with scores higher than the threshold value of 0.85, for which sensitivity, specificity and coverage were 86%, 68%, and 72%, respectively. We evaluated our method by comparing it with other scoring schemes and showed that reducing the noise inherent in experimental PPIs via our scoring scheme further increased the accuracy. Current study is expected to increase the efficiency of the methodologies in biological research which make use of protein interaction networks. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Protein interaction network; Protein-protein interactions; High-confidence; Saccharomyces cerevisiae; Yeast; INTERACTION MAP; NETWORKS; INSIGHTS; EXPRESSION; LANDSCAPE; INFERENCE; SCALE; SETS